GNE Myopathy in Turkish Sisters with a Novel Homozygous Mutation. (19th May 2016) - Diniz, Gulden; Secil, Yaprak; Ceylaner, Serdar; Tokucoglu, Figen; Türe, Sabiha; Celebisoy, Mehmet; İncesu, Tülay Kurt; Akhan, Galip
Abstract : Background . Hereditary inclusion body myopathy is caused by biallelic defects in the GNE gene located on chromosome 9p13. It generally affects adults older than 20 years of age. Methods and Results . In this study, we present two Turkish sisters with progressive myopathy and describe a novel mutation in the GNE gene. Both sisters had slightly higher levels of creatine kinase (CK) and muscle weakness. The older sister presented at 38 years of age with an inability to climb steps, weakness, and a steppage gait. Her younger sister was 36 years old and had similar symptoms. The first symptoms of the disorder were seen when the sisters were 30 and 34 years old, respectively. The muscle biopsy showed primary myopathic features and presence of rimmed vacuoles. DNA analysis demonstrated the presence of previously unknown homozygous mutations [c.2152 G>A (p.A718T)] in the GNE genes. Conclusion . Based on our literature survey, we believe that ours is the first confirmed case of primary GNE myopathy with a novel missense mutation in Turkey. These patients illustrate that the muscle biopsy is still an important method for the differential diagnosis of vacuolar myopathies in that the detection of inclusions is required for the definitive diagnosis.